Sleeping Disorders due to the Distress of War - Moroziuk Катерина (Psychosomatic Medicine and General Practice, 2023)
Topicality. With the start of the full-scale invasion of russia in Ukraine, sleeping disorders are becoming more and more widespread among the civil population – frequent air alarms at night, shelling of the civil areas, everyday loud sounds that are now perceived in a different way - these all cause sleeping disorders. Studies of the US researchers [1] prove that sleeping disorders, such as insomnia, short-term sleep, and nightmares in particular, are common at the time of military actions. This has an impact on people’s health and well-being by reducing muscular strength and impairing the nervous and cardiovascular systems. For many people involved in armed conflicts (servicemen, civilians living within the area of active combat actions, people under constant threat of air attacks, etc.) sleeping disorders last for many more years after and can have a considerable impact on their ability to reintegrate in society and have a normal life after war. As of today, there is little research in Ukraine which would describe sleeping disorders and sleep quality deterioration in the civilian population in wartime, features of sleep in wartime, and their correlation with psychopathological phenomena, such as anxiety and depression. Also, there is insufficient research of projected functional changes in the population emerging as a result of sleep-wake cycle disorders. All these define the topicality of this research. Aim of the research. The research aims to explore sleep quality deterioration in the civilian population living in Ukraine in wartime and identify correlation between sleep quality deterioration and symptoms of anxiety and depression. Methodology of the research. The clinical objects of the research are 103 respondents. In addition to the social demography method of study, the research made use of the Pittsburgh Sleep Quality Index (PSQI), Hospital Anxiety and Depression Scale (HADS), Quality of Life Scale (© by O. Chaban), as well as the methods of statistical data processing using the CORREL function in Excel tables. Results. In the course of the research it has been discovered that ⅔ of the respondents living in Ukraine in wartime show sleeping disorders of different severity. Positive direct medium-degree correlation has been established between sleep quality deterioration and elevated anxiety levels. The given research contains optimized recommendations for medical and psychological consultations aimed at improving sleep quality at the time of crisis and dealing with negative consequences of sleeping disorders.